Effect of HCO $ _3^ - $ on rice growth and iron uptake under flood irrigation and drip irrigation with plastic film mulch. Issue 6 (23rd October 2015) - Zhang, Xinjiang; Zhang, Shujie; Zhao, Honghua; Zhu, Qichao; Bai, Ruxiao; Yang, Yuzhen; Wang, Mei; Wang, Juan; Wei, Changzhou
Abstract: There has been a partial shift away from conventional flood irrigation (FI) practices for rice ( Oryza stativa L.) production in water‐scarce northern China. Drip irrigation with plastic film mulch (DI‐PFM) can maintain high rice yields with significant water savings. However, rice seedlings often develop chlorosis when grown with DI‐PFM on calcareous soil. Bicarbonate is a concern with regard to chlorosis in calcareous soil. The objective of this simulation experiment was to determine the effect of irrigation method and irrigation water HCO$ _3^ - $ concentration on (1) soil pH and DTPA‐Fe concentration, (2) chlorophyll, total Fe, and active Fe concentrations of rice leaves, and (3) rice root and shoot biomass. The experiment consisted of four treatments: FI with water containing either 2 or 10 mM HCO$ _3^ - $ (referred to as FI‐2 and FI‐10, respectively) and DI‐PFM with water containing 2 or 10 mM HCO$ _3^ - $ (referred to as DI‐2 and DI‐10, respectively). The results show that the HCO$ _3^ - $ concentrations of the soil solution were greater under FI than under DI‐PFM, because more irrigation water was applied in the FI system. Soil pH increased as the HCO$ _3^ - $ concentration of the irrigation water increased. The increase in soil pH was greater in DI‐PFM than in FI. Soil DTPA‐Fe concentration, leaf SPAD values, leaf total Fe concentration, leaf active Fe concentration, shoot biomass, and root biomass decreased as the HCO$ _3^ - $ concentration of the irrigation water increased. The decreases were less under DI‐PFM than under FI. Overall, the results indicate that rice plants are more sensitive to the HCO$ _3^ - $ concentration of irrigation water under FI than under DI‐PFM.